A randomised controlled trial of computer-assisted interviewing in sexual health clinics. - Richens, J; Copas, A; Sadiq, S; Kingori, P; McCarthy, O; Jones, V; Hay, P; Miles, K; Gilson, R; Imrie, J; Pakianathan, M (2010)
OBJECTIVES: To assess the impact of computer-assisted interview compared with pen and paper on disclosure of sexual behaviour, diagnostic testing by clinicians, infections diagnosed and referral for counselling. METHODS: Two-centre parallel three-arm randomised controlled open trial. Computer-generated randomisation with allocation concealment using sealed envelopes. SETTING: Two London teaching hospital sexual health clinics. PARTICIPANTS: 2351 clinic attenders over the age of 16 years. INTERVENTIONS: Computer-assisted self-interview (CASI). Computer-assisted personal interview (CAPI). Pen and paper interview (PAPI). MAIN OUTCOME MEASURES: Diagnostic tests ordered, sexually transmitted infections (STI). SECONDARY OUTCOMES: Disclosure of sexual risk, referral for counselling. RESULTS: 801, 763 and 787 patients randomly allocated to receive CASI, CAPI and PAPI. 795, 744 and 779 were available for intention-to-treat analysis. Significantly more diagnostic testing for hepatitis B and C and rectal samples in the CAPI arm (odds for more testing relative to PAPI 1.32; 95% CI 1.09 to 1.59). This pattern was not seen among CASI patients. HIV testing was significantly lower among CASI patients (odds for less testing relative to PAPI 0.73; 95% CI 0.59 to 0.90). STI diagnoses were not significantly different by trial arm. A summary measure of seven prespecified sensitive behaviours found greater reporting with CASI (OR 1.4; 95% CI 1.2 to 1.6) and CAPI (OR 1.4; 95% CI 1.2 to 1.7) compared with PAPI. CONCLUSION: CASI and CAPI can generate greater recording of risky behaviour than traditional PAPI. Increased disclosure did not increase STI diagnoses. Safeguards may be needed to ensure that clinicians are prompted to act upon disclosures made during self-interview.